Seksting and investigation of materials with child sexual abuse (Journal of Universal Excellence, 2026)
Research Question (RQ): How widespread is the phenomenon of sexting among young people? Are young people sufficiently aware about this subject? Any difficulties encountered when investigating sexting?Purpose: The purpose of this paper is to present problems in investigating sexting. Since using Internet child pornography expanded and changed the way the investigation of this crime, it is necessary to explore new ways of investigating and overcoming problems in the investigation of more attention.Method: The article is transparent and theoretical. It is based primarily on an analysis of available domestic and foreign literature and Internet sources on the issues addressed. Results: Showing sexting consequences of abuse, and also provides some preventive tips for safest use the Internet. In conclusion, the investigators also presented problems in the investigation of crimes related to sex abuse with minors.Society: The survey alert to be aware of the problem among young people. We emphasize the importance of raising awareness of young people and the importance of the application of possible abuse.Originality: The originality of the contribution is reflected in the examination of the current investigation sexting problems, faced by investigators on a daily basis. Only in this way it can eliminate problems and improve search.Limitations/Future Research: Using sexting appear high risk, but they are young without consulting the parents are not aware of. It is necessary to invest more effort into raising awareness of young people and create an environment that will encourage victims to report abuse.
Keywords: sexting; internet; social networks; consequences; prevention; investigation